Predictive Model of Risk Behaviour in the University Student Community - Wylęgły, Kamila (Journal of Education Culture and Society, 2024)
Aim. The study aimed to attempt to explain the probable causality of undertaken risk behaviours in a group of university students, from the perspective of various predictors (which included low individual and social resources, as well as other risk behaviours). The choice of predictors was dictated, among other things, by the assumptions of risk behaviour theory and gateway theory. Methods. The research was conducted among university students from many cities in Poland. Empirical data were collected using the survey method. The tool was a survey questionnaire, constructed from the author's scale and the Resilience Scale by Gail Wagnild in the Polish adaptation by Janusz Surzykiewicz and Karol Konaszewski (2019). The data were statistically analysed. The target procedure became path analysis.Results. The study revealed several plausible predictive factors for specific risk behaviours of students. Analyses included behavioural categories such as the use of psychoactive substances and behaviour associated with them, risky sexual contact, low physical and psychosocial health care, dangerous behaviour in daily life, and disclosure of images and private data on the Internet. Each form of risky behaviour was situated in the model. The predictive factors in the path structure were identified as, among others, low social and cultural resources and low levels of resilience. It also appeared that some risk behaviours may be predictors for others.Conclusion. The study reveals that not only syndromes of risk behaviours, but even entire risk pathways creating the possibility to infer probable causality, are noticeable in the group of university students.